Left Atrial Myxoma: A Rare Nonatherosclerotic Cause of Acute Myocardial Infarction - Rey Francisco Arcenas; Mir Ishtiaque Ali (Case Reports in Cardiology)
Myocardial infarction from coronary artery embolism is a very rare but potentially lethal sequel of left atrial myxoma. Most atrial myxomas causing myocardial infarction are diagnosed retrospectively after a 2D echocardiogram is performed for assessment of myocardial function after a myocardial infarction. We present a relatively healthy 53-year-old male with anterolateral wall myocardial infarction and 100% occlusion at the proximal part of the obtuse marginal branch of the circumflex coronary artery that was subsequently reperfused. A 2D echocardiogram performed two days later revealed a left atrial mass, which was successfully resected and proven to be a myxoma. No recurrence of the tumor was seen on follow-up after four months. An automatic implantable cardioverter defibrillator was placed for residual ischemic cardiomyopathy with clinical improvement.